2017
DOI: 10.1021/acssuschemeng.7b01186
|View full text |Cite
|
Sign up to set email alerts
|

Ball Milling for Biomass Fractionation and Pretreatment with Aqueous Hydroxide Solutions

Abstract: A promising approach in the selective separation and modification of cellulose from raw biomass under a mild alkali process was proposed. In our study, ball milling was applied to wheat straw prior to alkali treatment. With ball milling, ultrafine powder formed an amorphous microstructure and displayed a level of solubilization in aqueous NaOH higher than that of general ground samples. Alkali-treated ultrafine powder resulted in up to 93.76% removal of hemicellulose and 86.14% removal of lignin, whereas cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…They found that the deconvoluted NMR signal of C-4 region (80–92 ppm) gives key information on the specific cellulose fibril structure. The C-4 region divided into two distinct region ranges: crystalline region and amorphous region [ 27 ]. Region from 86 to 92 ppm represents cellulose in more ordered forms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the deconvoluted NMR signal of C-4 region (80–92 ppm) gives key information on the specific cellulose fibril structure. The C-4 region divided into two distinct region ranges: crystalline region and amorphous region [ 27 ]. Region from 86 to 92 ppm represents cellulose in more ordered forms.…”
Section: Resultsmentioning
confidence: 99%
“…However, cellulose, a homopolymer of glucose, has a compact fibril structure possessing high crystallinity and extensive hydrogen bonds that are formed during biosynthesis which hinders the cellulose conversion efficiency [ 5 , 6 ]. Pretreatment is required to make the compact cellulose structure accessible to enzyme or chemical catalyst to efficiently hydrolyze β-1,4 glycosidic bond [ 7 , 8 ]. Unlike pretreatments such as dilute acid, ammonia fiber expansion, ammonia recycle percolation pretreatment demanding high temperature or pressure, and cellulose solvent- and organic solvent-based lignocellulose fractionation (COSLIF) can fractionate lignocellulose components at modest reaction conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The D-value for the RCS was only 13.40% with the lowest biogas production. This indicates that the loss of cellulose and hemicelluloses of CS had been converted to biogas, and a larger D-value means more biogas production [55]. This also indicated that addition of NaOH and CaO can help more CS to be converted to reducing sugars for biogas production [9,32].…”
Section: Reducing Sugar and Lignin Content Of Cs After Digestingmentioning
confidence: 89%
“…They lead to structural disruption and reduction of the particle size and crystallinity of the raw material, which results in some improvement of the enzymatic digestibility. However, since the energy requirements for achieving high cellulose conversion are far too high, these methods are of interest only if used in combination with other techniques or as a preparative step before other processes are applied [35]. In biological pretreatment, the ligninolytic enzyme system of lignin-degrading microorganisms, especially white-rot fungi, is used to remove lignin from lignocellulose.…”
Section: Pretreatment For Enzymatic Saccharificationmentioning
confidence: 99%